Concentrations of retinol and carotenoids in Jersey milk during different seasons and possible application of the colour parameter as an indicator of milk carotenoid content - Kelava Ugarković, Nikolina (Array, 2020)
The aim of this study was to determine concentrations of retinol, β-carotene, lutein and zeaxanthin in Jersey milk during different seasons and their correlation with milk colour parameters. During a sixmonths period the Jersey cows (n=77) were kept free-stall and fed with total mixed ratio (TMR; farm season), for the next three months the cows were kept for four hours on pasture and the rest of the day free-stall fed with TMR (transition season), and for the remaining three months they were kept predominantly on pasture (grazing season). A bulk milk samples (200 mL) were collected during the last week of each month in the period between May 2018 and April 2019. Retinol and carotenoids concentrations in cow milk were quantified using high performance liquid chromatography, while milk chemical composition was analysed by a MilkoScan FT 120 infra-red analyser. The season significantly (P<0.05) affected chemical composition of milk, and the highest (P<0.05) content of milk fat, protein and non-fat dry matter was found during the farm season. Retinol, β-carotene, lutein and zeaxanthin concentrations (μg/100 mL) were as follows: 2.56±0.29, 4.15±0.27, 4.43±0.40 and 0.97±0.04. Lutein and retinol concentrations in Jersey milk were affected (P<0.05) by the season. The highest lutein concentration was found during the grazing season, while the farm season yielded the highest retinol concentration. Moderate and positive correlations (P<0.05) were found between β-carotene and lutein concentrations and colour parameter b*, resulting in a more intense yellow colour i.e. high values of colour parameter b*. The obtained results suggest that milk colour could be used to estimate carotenoid concentrations in milk.